Strategi Kepemimpinan Kepala Madrasah Dalam Meningkatkan Mutu Pendidikan Pada Masa Pandemi Covid-19 - Moh Nasiruddin; Abu Darim (Pedir Research Institute, 2023)
The leadership strategy is a series of certain ways or steps taken by leaders to influence individuals or groups so that they voluntarily carry out the goals to be achieved. In this case the policy taken by a leader to be followed by groups or individuals. The focus of this research is threefold, 1) What is the strategy of the head of madrasah at MTs Darul Ulum Rembang Pasuruan in improving the quality of content (curriculum) during the Covid-19 pandemic, 2) What is the strategy of the head of madrasah at MTs Darul Ulum Rembang Pasuruan in improving the quality of teaching staff (tendik). during the Covid-19 pandemic, 3) What is the strategy of the head of the Madrasah at MTs Darul Ulum Rembang Pasuruan in improving the quality of facilities and infrastructure (sapras) during the Covid-19 pandemic. In this study, the author uses a type of qualitative research with a qualitative descriptive approach. Data collected through observation, interviews and documentation. The validity of the data by means of triangulation. The results of the research found at the research location showed that the principal's strategy in improving the quality of education during the covid-19 pandemic was quite successful, the strategies used included, among others, forming an emergency curriculum development team, making lesson plans adapted to local culture, in learning carried out by remotely, and 50% face-to-face by complying with health protocols. In addition, increasing educators and education staff by always including training if there are workshops or participating, in improving facilities and infrastructure, namely by coordinating at the beginning of the new school year, determining planning and implementation, the results of coordination are the procurement of masks, hand sanitizer, soap and washing facilities. hand. As well as adding wifi capacity, in addition to improving infrastructure such as furniture, adding computers and laptops, and LCD projectors.